Peningkatan Keterampilan Pemasaran Berbasis Digital pada Pelaku UMKM Pondok Bambu, Duren Sawit Jakarta Timur - Erik, Erik; Suryaratri, Ratna Dyah; Deasyanti, Deasyanti (Empowerment, 2022)
The purpose of this community empowerment activity is to improve digital-based marketing skills. This activity is expected to be able to provide practical skills to UMKM in Pondok Bambu Duren Sawit, East Jakarta. The method used in this community empowerment is in the form of seminars presented by digital marketing experts. Participants were given a survey before and after participating in seminar activities aimed at seeing whether there was an increase in knowledge related to digital marketing after the exposure was given. The result of this activity is that participants have a knowledge score related to digital-based marketing which increases from the results before and after participating in digital-based marketing seminars. Furthermore, it is hoped that this knowledge can be used as initial capital to apply their skills in marketing digital-based products or services.